Electrochemical Detection and Characterisation of Polymer Nanoparticles - Zhou, X; Cheng, W; Batchelor-McAuley, C; Tschulik, K; Compton, R (2014)
We report the detection and characterisation of polymer nanoparticles using electrochemistry using poly(N-vinylcarbazole) nanoparticles (PVK NPs) as a model system. These were synthesised using the reprecipitation method. The number of electrons (n=2) transferred per PVK monomer was characterised by drop-casting method. Sticking and sensing experiments were then conducted, which involve PVK nanoparticle immobilisation on the electrode surface and subsequent oxidative sensing, to enable rapid detection of polymer nanoparticles in aqueous solution. It is shown for the first time, that using this "stick and sense" method, polymer nanoparticles in aqueous solution can be immobilised, preconcentrated and quantified. © 2014 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.